2015
DOI: 10.3233/bme-151287
|View full text |Cite
|
Sign up to set email alerts
|

Color difference threshold determination for acrylic denture base resins

Abstract: Abstract. This study aimed to set evaluation indicators, i.e., perceptibility and acceptability color difference thresholds, of color stability for acrylic denture base resins for a spectrophotometric assessing method, which offered an alternative to the visual method described in ISO 20795-1:2013. A total of 291 disk specimens 50±1 mm in diameter and 0.5±0.1 mm thick were prepared (ISO 20795-1:2013) and processed through radiation tests in an accelerated aging chamber (ISO 7491:2000) for increasing times o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…In the present study, resins (bis‐acryl and flowable resin) from the same manufacturer and from the same batch were selected. Although they are commercialized in the same color (A2), the results suggest a different colorimetric behavior among the materials, which may result in a clinical problem, because the differences found are higher than the acceptable thresholds described in the literature …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, resins (bis‐acryl and flowable resin) from the same manufacturer and from the same batch were selected. Although they are commercialized in the same color (A2), the results suggest a different colorimetric behavior among the materials, which may result in a clinical problem, because the differences found are higher than the acceptable thresholds described in the literature …”
Section: Discussionmentioning
confidence: 99%
“…Ren et al provided perceptibility threshold (PT)/acceptability threshold (AT) for acrylic resins (1.7/4.0 Δ E 00 ) using the CIEDE 2000 formula. If we compare the results found in the present study with those thresholds proposed, the color differences found between the groups (BCR‐BCR = 1.2, BCR‐FR = 5.6, and BCR‐AFR = 5.0 Δ E 00 ) were perceptible and acceptable only for the group repaired with the same bis‐acryl composite resin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] After baseline hardness measurement, discs were thermocycled in a thermocycling simulation machine (MSCT-3, Convel, Aracatuba, Sao Paulo, Brazil).…”
Section: Methodsmentioning
confidence: 99%
“…Several nanoscale pigments as dark carbon (C), zinc oxides (ZnO), titanium (Ti), and iron (Fe) have been incorporated into acrylic resins for improving the esthetic of the denture base. [23]…”
Section: Introductionmentioning
confidence: 99%